CONTEMPORARY MANAGEMENT OF COMMERCIAL BANKS - Kirdasinova К.А.; Sabirova R.K.; Aibossynova D.A.; Kabdullina G.К. (Scientific Journal of Pedagogy and Economics, 2020)
The development of a market economy is characterized by instability of both external and internal organizational environment, which leads to the succession of the influence of the compared competitive advantages of credit and financial market entities on the formation of their competitive positions, which, in turn, means that the competitiveness of banks, like other financial institutions, is a relative concept. Competition is a rather subtle and flexible concept. In conditions of reduced demand for banking products and services, banking organizations that provide low-quality banking services are experiencing the greatest difficulties. With all of the scale of competition, the bank that analyzes and fights for its competitive position wins. The article explains and studies the reasons for the low competitiveness of banks in the modern banking system, which characterize the inability of banks to uphold and expand market share, promote banking products, and fully satisfy consumer interests. It is revealed that at the present stage, a quantitative assessment of the level of competitiveness of products and services of a bank and its management becomes an important issue, since it is a rather laborious, integrated process consisting of interconnected components and on which the competitiveness of the entire bank depends. On the basis of the study, relevant conclusions were identified.